(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
Background:The color stability of aesthetic arch wires is an important factor in the success of an aesthetic orthodontic treatment, but the color of these arch wires tends to change with time.This study was performed to assess the effect of two types of mouth washes on the color stability of different types of aesthetic arch wires at different time intervals. Materials and methods:Four brands of nickel titanium coated aesthetic arch wires were used: epoxy coated (Orthotechnology and G&H) and Teflon coated (Dany and Hubit).Thirty six samples were prepared, each sample contains ten halves of the aesthetic arch wires. They were divided into three groups according to the immersion media (distilled water as a control media, Listerine with fluoride and Listerine without fluoride) and immersed for 30 seconds twice daily according to manufacturer’s instructions to measure color change after 1 week, 3 weeks and 6 weeks by using spectrophotometer VITA Easyshade Compact according to Commission Internationale de l’Eclairage L*a*b* color space system. Results:It was found that there were highly significant differences in color change values of aesthetic arch wires among all immersion media at different time intervals and color change value increases as the time of immersion increases.Additionally, Listerine with fluoride mouth wash caused higher color change values of aesthetic arch wires than Listerine without fluoride and Hubit aesthetic arch wires were the least color stable while Orthotechnology aesthetic arch wires were the most color stable. Conclusions: We can conclude that the daily use of Listerine mouth washes could affect on the color stability of aesthetic arch wires. Although all tested aesthetic arch wires revealed color changes at variable degrees but some of these changes were not visible and the others were clinically acceptable while the remaining were clinically unacceptable.